Ide Kebangsaan dalam Puisi Antara Sajak-sajak M. Yamin dan Sejumlah Sajak Karya Penyair Malaysia - Wasono, Sunu (Wacana, Journal of the Humanities of Indonesia, 2004)
show that Indonesian and Malaysian literatures grew and developed out of the same old tradition, namely Malay tradition. Indonesian and Malaysian languages are also rooted in the same language, namely, the Malay language. It only makes sense that there a number of similarities This paper discusses the nationalist ideas found in the poems of M. Yamin published in Indonesia Tumpah Darahku and a number of poems produced by 10 Malaysian poets. These Malaysians' poems are found in a poetry anthology titled Puisi-puisi Kebangsaan 1913-1957 (nationalist poems 1913-1957) compiled by Abdul Latif Abu Bakar and published in 1987. Based on a comparison of these two sets of poems, some similarities can be discerned, such as admiration of natural beauty, admiration of past heroes and glories, and appeal by the poets for national unity. These similarities are made possible by similar political and cultural situations prevailing in both Indonesia and Malaysia in certain period of time. The relation between Indonesia and Malaysia that is tied by a common language (Malay) and a sense of being in the same situation (colonial oppression) are other factors that allow a number of Indonesian and Malaysian poets to write poems of similar themes in similar styles.